Sedimentary phosphorus burial in three contrasting boreal lakes in Finland - Laakso Johanna; Jilbert Tom; Saarinen Timo (SPRINGER JAPAN KK, 2025)
Permanent phosphorus (P) burial in sediment regulates lake trophic state over long timescales, but the controls on P burial are only partially understood. A diversity of biogeochemical settings may be found in lake sediments, which may have a strong impact on the processes controlling P burial from one location to another. Here, we investigate early diagenesis of P in three contrasting lakes in Southwest Finland. Eutrophic Lake Koylionjarvi and mesotrophic Lake Pyhajarvi have a history of nutrient loadings from agriculture, while Lake Vahajarvi is an oligotrophic small forest lake, leading to potentially contrasting sediment biogeochemical dynamics. We combined porewater data and solid-phase sediment geochemical data to identify P phases in each system and investigate the dominant processes controlling P burial. Porewater profiles showed opposite gradients between the oligotrophic and the mesotrophic/eutrophic systems, implying net diffusive fluxes into and out of the sediments, respectively. Furthermore, sediment P data showed contrasting P speciation. Reactive P is buried in all systems, but the role of reducible iron (Fe) oxides in P retention is greater in mesotrophic/eutrophic lakes. In the oligotrophic system, aluminium (Al) oxides controlled P sorption into the sediment after diffusion from lake water. Evidence for vivianite formation was found only in the mesotrophic Lake Pyhajarvi sediment, where 42-47% of total P was released in a Fe(II)-P specific extraction from the deeper part of the sediment column and vivianite crystals could be isolated from sediment samples.